Marital Adjustment and Spouses’ Ratings of their own and their Partners’ Specific Affects During a Conversation - Wilson Alcalde, Juan; Mejía Paredes, Juan (Revista de Psicología, 2002)
Previous studies have shown an association between marital adjustment and selfrating or partner’s rating of affect during a marital conversation. However, such assessments of the conversation have been restricted to the global categories of positive and negative affect. In this study, 60 persons rated every minute of their marital conversation in terms of their own and their partners’ experience on 7 specific emotions: anger, sadness, fear, interest, joy, love and calmness. A subset of these variables accounted for 64% of wife marital adjustment and another accounted for 70% of husband marital adjustment.